Developing nursing students' self-efficacy and problem solving skills via high-fidelity simulation - Cengiz, Zeliha; Gurdap, Zuleyha; Oltuluoglu, Hatice; Aslan, Hakime; Aktura, Seher Cevik (Elsevier Science Inc, 2023)
The research was conducted to examine the effect of using high-fidelity simulation on students' problemsolving skills and self-efficacy. This randomized controlled study was conducted with 112 first-year students. The post-test self-efficacy score was higher in the experimental group than in the control group. The posttest problem solving score was lower in the experimental group than in the control group. Use of high-fidelity simulation in nursing education improved students' self-efficacy and problem-solving skills. (c) 2023 Organization for Associate Degree Nursing. Published by Elsevier Inc. All rights reserved.
Keywords: High-fidelity simulation; Nursing students; Problem solving skill; Self-efficacy; Simulation